Analysis of CP Violation in D0→K+K-π0. (22nd November 2018) - Zhou, Hang; Zheng, Bo; Zhang, Zhen-Hua
Abstract : We study the C P violation induced by the interference between two intermediate resonances K ⁎ ( 892 ) + and K ⁎ ( 892 ) - in the phase space of singly-Cabibbo-suppressed decay D 0 → K + K - π 0 . We adopt the factorization-assisted topological approach in dealing with the decay amplitudes of D 0 → K ± K ⁎ ( 892 ) ∓ . The C P asymmetries of two-body decays are predicted to be very tiny, which are ( - 1.27 ± 0.25 ) × 1 0 - 5 and ( 3.86 ± 0.26 ) × 1 0 - 5, respectively, for D 0 → K + K ⁎ ( 892 ) - and D 0 → K - K ⁎ ( 892 ) +, while the differential C P asymmetry of D 0 → K + K - π 0 is enhanced because of the interference between the two intermediate resonances, which can reach as large as 3 × 1 0 - 4 . For some NPs which have considerable impacts on the chromomagnetic dipole operator O 8 g, the global C P asymmetries of D 0 → K + K ⁎ ( 892 ) - and D 0 → K - K ⁎ ( 892 ) + can be then increased to ( 0.56 ± 0.08 ) × 1 0 - 3 and ( - 0.50 ± 0.04 ) × 1 0 - 3, respectively. The regional C P asymmetry in the overlapped region of the phase space can be as large as ( 1.3 ± 0.3 ) × 1 0 - 3 .